Shorting in Broad Daylight: Short Sales and Venue Choice - Reed, Adam V.; Samadi, Mehrdad; Sokobin, Jonathan S. (Journal of Financial and Quantitative Analysis, 2020)
Using a novel database on venue short sales and market design characteristics, we ask: Where do short sellers exploit their information advantage? Consistent with the prediction of Zhu (2014), we find that exchange short sales comprise a larger proportion of trading and are more informative about future prices than dark-pool short sales, particularly when there is greater competition among short sellers to trade and in the presence of short-lived information. When examining market design characteristics, we find that dark pools offering volume-weighted average price crossing attract more short sales, whereas those offering block trading attract fewer short sales.